Knowledge and Attitudes towards Dementia among Clinical Years Medical Students at Jazan University: A Cross-sectional Study - Elmahdy, Mona H.; Ajeebi, Maryam E.; Hudisy, Arwa A.; Madkhali, Jnadi M.; Madkhali, Athar M.; Hakami, Ammar A. (International Journal of Innovative Research in Medical Science, 2020)
Background: The literature suggests that training in dementia among medical students appears to be inadequate. This study aimed to evaluate medical students’ knowledge and attitudes toward dementia. Aim: To assess knowledge and attitudes of Saudi medical students towards dementia. Methods: This cross-sectional study was conducted at College of Medicine, Jazan University, Jazan, Saudi Arabia using a sample of 241 medical students from clinical years (4th, 5th, and 6th). A structured and self-assessment questionnaire was used and included the socio-demographic data and questions related to knowledge and attitudes toward dementia. Data were presented as frequency and percentage, and as mean and standard deviation (SD). Results: A total of 241 participants agreed to take part in our study; 155 (64.3%) of them were females. Only 44 (18.3%) participants stated that they had a good training in dementia (mostly theoretical, 16.6%) and 17 (7.1%) mentioned having an extracurricular course in the subject. Out of 14 questions, participants obtained a mean of 1.49 (SD = 1.48). Regarding attitudes, participants agreed that much can be done to improve the quality of life of patients with dementia and their caregivers, that it is useful to provide the diagnosis of dementia to the family, and that dementia is better diagnosed in specialized service units. Conclusions: The findings of the present study suggest that while medical students generally have positive attitudes toward dementia, they have poor knowledge about the subject. More effort is needed to bridge knowledge gaps in dementia understanding at undergraduate level.